2023
DOI: 10.1038/s41419-023-05590-w
|View full text |Cite
|
Sign up to set email alerts
|

PTK6 inhibits autophagy to promote uveal melanoma tumorigenesis by binding to SOCS3 and regulating mTOR phosphorylation

Abstract: Autophagy dysfunction is one of the common causes of tumor formation and plays an important role in uveal melanoma (UM). However, little is known about the regulatory mechanisms of autophagy in UM. Here, we show that PTK6 can promote the proliferation, migration, and invasion of UM cells by inhibiting autophagy. SOCS3 can inhibit the proliferation, migration, and invasion of UM cells. Overexpression of SOCS3 can partially rescue the PTK6-induced promotion of UM cell proliferation, migration, and invasion. Mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…PTK6, a member of the tyrosine kinase family, inhibits autophagy through the mTOR pathway, which further promotes the progression of UM. PTK6 is also highly expressed in UM samples and correlates with the prognosis of tumour patients, and experiments in nude mice have demonstrated that PTK6 promotes the growth of UM (Liu et al 2023b ). LINC01278 is lowly expressed in UM, and the tumour patients with high expression of LINC01278 have a better prognosis.…”
Section: Studies On Autophagy and Ummentioning
confidence: 99%
“…PTK6, a member of the tyrosine kinase family, inhibits autophagy through the mTOR pathway, which further promotes the progression of UM. PTK6 is also highly expressed in UM samples and correlates with the prognosis of tumour patients, and experiments in nude mice have demonstrated that PTK6 promotes the growth of UM (Liu et al 2023b ). LINC01278 is lowly expressed in UM, and the tumour patients with high expression of LINC01278 have a better prognosis.…”
Section: Studies On Autophagy and Ummentioning
confidence: 99%
“…Although PTK6 has been explored in other cancers, its involvement in UM is yet to be fully elucidated. However, Liu et al reported that increased PTK6 expression in UM cells was associated with a poor prognosis [87]. Increased PTK6 activates mTOR and in turn, increases tumorigenesis by promoting the proliferation, migration, and invasion of UM cells and inhibiting autophagy [87].…”
Section: Protein Based Um Autophagy Biomarkersmentioning
confidence: 99%
“…However, Liu et al reported that increased PTK6 expression in UM cells was associated with a poor prognosis [87]. Increased PTK6 activates mTOR and in turn, increases tumorigenesis by promoting the proliferation, migration, and invasion of UM cells and inhibiting autophagy [87]. PTK6 binds to SOCS3 in UM cells, so that targeting the SOCS3-PTK6 signalling axis might be a novel and promising therapeutic strategy for patients with UM [87].…”
Section: Protein Based Um Autophagy Biomarkersmentioning
confidence: 99%
“…Since PTK6 activates STAT3 and STAT3 induces SOCS3 expression, this results in a negative feedback mechanism to control PTK6 activity [96]. A very recent study on uveal melanoma cells demonstrates that overexpression of SOCS3 can partially inhibit the PTK6-driven uveal melanoma cell proliferation [104].…”
Section: Biological Inhibitorsmentioning
confidence: 99%